2001
DOI: 10.1177/002215540104900812
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic Anhydrase II Associated with Plasma Membrane in a Human Pancreatic Duct Cell Line (CAPAN-1)

Abstract: S U M M A R YThe subcellular distribution of carbonic anhydrase II, either throughout the cytosol or in the cytoplasm close to the apical plasma membrane or vesicular compartments, suggests that this enzyme may have different roles in the regulation of pH in intra-or extracellular compartments. To throw more light on the role of pancreatic carbonic anhydrase II, we examined its expression and subcellular distribution in Capan-1 cells. Immunocytochemical analysis by light, confocal, and electron microscopy, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…In the immunohistochemistry analysis, CA-II expression was localized to the membrane of the tumor endothelium. CA-II may be attached to the inner leaflet of the membrane as shown in a pancreatic cancer cell line (36). However, it is still possible that CA-II expressed in the endothelium is targeted by the immune system because mouse models have shown that immunization with CA-II induced sialoadenitis (37), cholangitis (38), and pancreatitis (39) by targeting CA-II expressed in each organ.…”
Section: Discussionmentioning
confidence: 99%
“…In the immunohistochemistry analysis, CA-II expression was localized to the membrane of the tumor endothelium. CA-II may be attached to the inner leaflet of the membrane as shown in a pancreatic cancer cell line (36). However, it is still possible that CA-II expressed in the endothelium is targeted by the immune system because mouse models have shown that immunization with CA-II induced sialoadenitis (37), cholangitis (38), and pancreatitis (39) by targeting CA-II expressed in each organ.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that this CA IV could be the extracellular component of an HCO 3 2 transport metabolon in association with cytosolic CA II and HCO 3 2 /Cl 2 exchanger. Indeed, we have described in Capan-1 cells the presence of a CA II associated with the cytosolic leaflet of apical plasma membranes (Alvarez et al 2001), andCheng et al (1998) have proposed the involvement of an apical Cl 2 /HCO 3 2 exchanger in Cl 2 and HCO 3 2 secretion in these cells. The functionality of such a complex has been demonstrated in transfected HEK293 cells (Sterling et al 2002).…”
Section: Discussionmentioning
confidence: 92%
“…The specificity of these two antibodies was established by the absence of cross-reaction with two CA isoforms expressed in Capan-1 cells, CA II Alvarez et al 2001) and CA IX (unpublished data), and by the recognition of a recombinant secreted form of human CA IV, which is normally GPI-anchored, by the CA IV NH 2 antibody and not the CA IV COOH antibody. These two antibodies revealed the presence of two CA IV-immunoreactive proteins with apparent molecular mass of 55 kDa and 35 kDa in Capan-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, experimental evidences have been presented revealing that the CAs might be involved in bone formation [35]. The mammalian CA-II, a cytosolic enzyme, is targeted in intact cell systems under certain physiological conditions to the cell membrane [3637]. …”
Section: Reviewmentioning
confidence: 99%
“…We have taken this observation as a further indication that carbonate and phosphate deposits are co- or sequentially synthesized onto SaOS-2 cells, during the initial phase of mineral formation. Furthermore, the CA-II has been proven to be (under certain physiological conditions [pH regulation]) localized at the plasma membranes of human pancreatic cells [36], where the enzyme is involved both in pH regulation and in the secretion of bicarbonate through the Cl − /HCO − exchanger [57] and/or an additional HCO 3 − channel [36]. We concluded from the data gathered [20] that the calcium phosphate/HA deposition reactions in bone tissue are preceded by calcium carbonate precipitation, a process that is driven by an increased CA activity (Fig.…”
Section: Reviewmentioning
confidence: 99%